Falsafah Insaniyah Dan Implikasinya Terhadap Pendidikan Islam - Taufiqur Rahman (Yayasan Rahmat Islamiyah, 2022)
Basically every human being is born in a state of nature. This means that humans are born in a weak state even though they have great potential. But that does not mean that humans are born like white paper or blank as John Lock said or are powerless according to Jabariyah's view. This is because humans have the potential in the form of certain tendencies regarding reasoning, mental, and psychic powers of different types and levels. The understanding of Islamic education experts about the nature of nature has implications for the birth of the theory of nature in education. In the context of education, theory becomes a foothold in developing human nature. In this case, the education process is important to improve its quality because it is one of the means that can grow and develop the potentials that exist in humans in accordance with the nature of their creation. This article discusses the philosophical review of human nature in the context of Islamic education.